2016
DOI: 10.1210/en.2015-1675
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Oral Administration of a Pan-Retinoic Acid Receptor Antagonist Inhibits Spermatogenesis in Mice With a Rapid Recovery and Changes in the Expression of Influx and Efflux Transporters

Abstract: We have previously shown that oral administration of a pan-retinoic acid receptor antagonist in mice daily at 2.5 mg/kg for 4 weeks reversibly inhibited spermatogenesis, with no detectable side effects. To elucidate the lowest dose and the longest dosing regimen that inhibits spermatogenesis but results in complete restoration of fertility upon cessation of administration of the drug, we examined the effects of daily doses as low as 1.0 mg/kg with dosing periods of 4, 8, and 16 weeks. We observed 100% sterilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
1
31
0
2
Order By: Relevance
“…In the 1980s, Huang and Marshall [162] suggested that vitamin A deficiency may delay spermiation. Moreover, ablation of RARs or RA-synthesizing enzymes (in germ cells and/or Sertoli cells) causes a variety of defects in both meiotic and postmeiotic transitions, including spermiation [63,[163][164][165][166][167][168]. A recent study has shown that RA plays primary roles at two postmeiotic transitions; the initiation of spermatid elongation and spermiation ( Figure 5) [19].…”
Section: Role Of Ra At the Initiation Of Spermatid Elongation And Spementioning
confidence: 99%
“…In the 1980s, Huang and Marshall [162] suggested that vitamin A deficiency may delay spermiation. Moreover, ablation of RARs or RA-synthesizing enzymes (in germ cells and/or Sertoli cells) causes a variety of defects in both meiotic and postmeiotic transitions, including spermiation [63,[163][164][165][166][167][168]. A recent study has shown that RA plays primary roles at two postmeiotic transitions; the initiation of spermatid elongation and spermiation ( Figure 5) [19].…”
Section: Role Of Ra At the Initiation Of Spermatid Elongation And Spementioning
confidence: 99%
“…Given that the two postmeiotic transitions—initiation of spermatid elongation and release of spermatozoa—coincide with high RA levels, we considered the possibility that RA might also regulate these two transitions. Indeed, ablations of RA receptors (RARs) or RA-synthesizing enzymes (in germ cells and/or Sertoli cells) cause a variety of modest defects in meiotic and postmeiotic aspects of spermatogenesis, including release of spermatozoa ( 23 29 ). Nonetheless, the specific steps in meiotic progression or postmeiotic differentiation that RA might regulate have not been established.…”
mentioning
confidence: 99%
“…For example, 2 groups of 30 mice each were administered BMS‐189453 at a dose of 5 mg/kg for 2 weeks followed by a dose of 2.5 mg/kg for 4 weeks. The mice treated in this study were completely sterile by 4 weeks . Twelve weeks after treatment was stopped, fertility was completely restored in all male mice.…”
Section: Experimental Male Contraceptivesmentioning
confidence: 73%
“…The mice treated in this study were completely sterile by 4 weeks. 82 Twelve weeks after treatment was stopped, fertility was completely restored in all male mice. This compound, or a more specific retinoic acid-alpha antagonist reported in the literature, 83 holds promise for nonhormonal male contraception.…”
Section: Review Of Current and Future Methods Of Male Contraception Amentioning
confidence: 96%